2020
DOI: 10.1002/fes3.237
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and physiological bases for variation in water use efficiency in canola

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 76 publications
3
19
0
Order By: Relevance
“…Farquhar and Richards (1984) proposed Δ 13 C as a time-integrated surrogate trait for measuring TE both at the single leaf level and at the whole plant level, as C 3 plants discriminate less against 13 C during photosynthesis with increased water deficit stress. The negative relationship between WUE and Δ 13 C has been verified in A. thaliana (Masle et al, 2005) and in some agricultural crop plants (Farquhar et al, 1982; Ehleringer, 1993; Hall et al, 1994; Rebetzke et al, 2008; Des Marais et al, 2014; Raman et al, 2019), with some exceptions where nil or weak associations were observed (Hammer et al, 1997; Monneveux et al, 2007; Devi et al, 2011; Raman et al, 2020b).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…Farquhar and Richards (1984) proposed Δ 13 C as a time-integrated surrogate trait for measuring TE both at the single leaf level and at the whole plant level, as C 3 plants discriminate less against 13 C during photosynthesis with increased water deficit stress. The negative relationship between WUE and Δ 13 C has been verified in A. thaliana (Masle et al, 2005) and in some agricultural crop plants (Farquhar et al, 1982; Ehleringer, 1993; Hall et al, 1994; Rebetzke et al, 2008; Des Marais et al, 2014; Raman et al, 2019), with some exceptions where nil or weak associations were observed (Hammer et al, 1997; Monneveux et al, 2007; Devi et al, 2011; Raman et al, 2020b).…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies revealed that canola lines display a range of variation in Δ 13 C (18.7 to 23.7‰). Triazine tolerant (TT) accessions show higher Δ 13 C values compared to conventional open-pollinated varieties and hybrids (Matus et al, 1995; Pater et al, 2017; Hossain et al, 2020; Raman et al, 2020b). In this study, we utilised non-TT accessions for genetic analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genetic control of water-use traits has been investigated in wheat, rice, maize, barley, tobacco, Arabidopsis, grape, soybean, sorghum, canola and cotton, with some progress made in elucidating the physiological relationship between yield and water limitation and identification of quantitative trait loci (QTL) for WUE traits [21][22][23][24][25]. Cultivars with enhanced production in water-limited environments have also been identified [26][27][28], but progress overall has been slow in deploying new fit-for-purpose varieties.…”
Section: Introductionmentioning
confidence: 99%